Pharmacist‐led intervention on chronic pain management: A systematic review and meta‐analysis. Issue 8 (24th February 2021) - Thapa, Parbati; Lee, Shaun Wen Huey; KC, Bhuvan; Dujaili, Juman Abdulelah; Mohamed Ibrahim, Mohamed Izham; Gyawali, Sudesh
Abstract : Aims: Pharmacists have been contributing to the management of chronic pain, ensuring the quality use of medicine. However, there is diversity in the interventions provided by pharmacists and their impact. Methods: Six electronic databases were searched from inception until June 2020 for articles published in English examining the intervention provided by the pharmacist in chronic pain management. Studies investigating the impact of pharmacist intervention individually or multidisciplinary teams including pharmacists for chronic pain management were included. Results: Fourteen studies (2365 participants) were included in the current review. Six studies were randomized controlled trials while the remainder were observational studies in which pharmacists provided intervention individually or in collaboration with other healthcare professionals. Medication review was the most common intervention provided by the pharmacist. The pooled analysis found that pharmacist‐led interventions reduced the pain intensity (−0.22; 95% confidence interval [CI]: −0.35 to −0.09; moderate certainty) among participants with chronic pain. Opiate stewardship provided by pharmacists was effective; however, mixed results were noted on the impact of the intervention on physical functioning, anxiety, depression and quality of life. Pharmacist intervention was more expensive than treatment as usual. Conclusions: Pharmacists contribute substantially to chronic pain management, ensuring the quality use of medicine, resulting in reduced pain intensity. Further studies with rigorous design are needed to measure the impact of pharmacist‐provided intervention individually or in a multidisciplinary team on the economic benefit and other health outcomes.